A case study on experimental and statistical analysis of energy consumption of domestic refrigerator. (December 2021) - Borikar, Sanjaykumar A.; Gupta, Mahendra M.; Alazwari, Mashhour A.; Malwe, Prateek D.; Moustafa, Essam B.; Panchal, Hitesh; Elsheikh, Ammar
Abstract: This paper presents the energy consumption analysis of the refrigerator and the effect of the condenser on it. According to the Bureau of Energy Efficiency (BEE), India, the energy efficiency of electric appliances is the key parameter for testing their performance before domestic use. For energy consumption analyses, the experimentation was conducted on the domestic refrigerator (165 L) top-mounted evaporator by retrofitting the refrigerator with an Elliptical Helical Coil Condenser (EHCC) and existing refrigerator with a Straight Tube Condenser (STC). Box-Behnken Design (BBD) is very significant in determining the significant factor and reducing the number of experiments. BBD has been performed to analyze the significance of factors ambient temperature, fresh food compartment temperature and the heat load in energy consumption, and the Coefficient of Performance (COP) of a refrigerator. The heat load and the ambient temperature are both very significant in determining the refrigerator's energy consumption. The most important thing is to increase the liquid content in the charge before it is supplied to the evaporator to extract more amount of heat to increase the cooling effect. The ANOVA (Analysis of Variance) results show that the ambient temperature and the heat load were more significant in increasing energy consumption and decreasing the COP and vice versa. The results of ANOVA and the experiment are very close; the R 2 value 0.995 precisely matches the R 2 adj. value 0.994. The statistical analysis using the Box-Behnken design produces a good fitting of the modeled and experimental data set. The present study aims to examine the effects of said factors and the condenser on the domestic refrigerator's energy consumption and COP. The study exhibits some enhancement in the COP to 2.59 contrary to 2.45 and energy consumption reduced to 1191 Wh from 1755 Wh during the trial of 24 h.